Corak Pemahaman dalam Visualisasi Hadis: Studi Kasus Animasi Hadis pada Channel Youtube CulapCulip - Andi Mujahidil Ilman SM, (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2024)
The rapid progress of information technology has made people make more use of online media in carrying out their daily activities. The ease of access to communication through online media makes Indonesia the country with the fourth ranking of internet users in the world. There are various social media platforms that can be used to find information, including YouTube. Apart from being a learning medium, YouTube has become a means for everyone to get the information they need from various parts of the world. Islamic Da'wah content is often found in YouTube uploads, both in the form of recordings and animations. "CulapCulip" is a YouTube channel that seeks to spread Islamic teachings using animated content. This research aims to analyze the patterns of understanding depicted in the hadith visualization by the YouTube channel "CulapCulip". This type of research is descriptive qualitative while the data analysis technique used is content analysis. This research technique is used to produce an objective and systematic description of the content contained in the YouTube channel. This research found that "CulapCulip" tries to visualize the hadiths of the Prophet with meanings that are in accordance with the reception of the understanding of hadiths in Indonesia. This research also found that "CulapCulip" attempted to visualize the Prophet's hadith contextually by considering the context of the hadith during the time of the Prophet (asbab al-wurud) and its implementation today. "CulapCulip" has succeeded in presenting a relatively new approach in providing an understanding of the Prophet's hadith in the form of animation through YouTube channel.